Perencanaan Jaringan Pipa Penyaluran Air Buangan Terpusat Di Rw Viii Kelurahan Menteng Kota Palangka Raya - Adetia Pahlevi (Universitas Bojonegoro, 2023)
Abstract: Palangka Raya as the capital city of Central Kalimantan is currently undergoing an urban development process, which has resulted in many land changes. One way to handle domestic liquid waste is by managing greywater. Greywater is domestic liquid waste that comes from several liquid wastes, other than toilet or toilet waste. Greywater can be produced from water used for bathing, water used for washing clothes, water used for washing equipment, and others. Based on PERDA City of Palangka Raya No. 1 of 2019 concerning Spatial and Regional Plans for the City of Palangka Raya for 2019-2039, the establishment of a wastewater disposal system through domestic WWTP is directed to large-scale new residential development areas, one of which is in Jekan Raya District. The purpose of this plan is to plan a pipe network for the distribution of exhaust air so that the drainage channels can accommodate the discharge of water in the rainy season and reduce environmental degradation. Keywords: Wastewater, Centralized domestic WWTP, Pipes Abstrak: Palangka Raya sebagai ibukota Kalimantan Tengah sekarang ini sedang mengalami proses pembangunan perkotaan, yang mengakibatkan banyaknya perubahan fungsi lahan. Salah satu cara penanganan limbah cair domestik dengan melakukan pengelolaan greywater. Greywater merupakan limbah cair domestik yang berasal dari beberapa limbah cair, selain limbah toilet atau kakus. Greywater dapat dihasilkan dari air bekas mandi, air bekas mencuci baju, air bekas mencuci peralatan, dan lainnya. Berdasarkan PERDA Kota Palangka Raya No 1 Tahun 2019 tentang Rencana Tata Ruang dan Wilayah Kota Palangka Raya tahun 2019-2039, penetapan Sistem pembuangan air limbah melalui IPAL domestik terpusat yang diarahkan untuk kawasan pengembangan pemukiman baru skala besar salah satunya berada di Kecamatan Jekan Raya. Tujuan dalam perencanaan ini untuk merencanakan Jaringan Pipa Penyaluran air buangan terpusat agar saluran drainase dapat menampung debit air musim hujan serta mengurangi penurunan kualitas lingkungan. Kata kunci:Air Buangan, IPAL domestik Terpusat, Pipa